A noncanonical amino acid-based relay system for site-specific protein labeling. Issue 52 (13th June 2018) - Chen, Yuda; Loredo, Axel; Gordon, Aviva; Tang, Juan; Yu, Chenfei; Ordonez, Janett; Xiao, Han
Abstract : A noncanonical amino acid-based relay system spanning the biosynthesis, incorporation, and bioconjugation of p -aminophenylalanine was developed for site-specific protein labeling. Abstract : Genetically site-specific introduction of noncanonical amino acids (ncAAs) for protein conjugation generally requires incorporation through exogenous feeding of chemically synthesized ncAAs. We developed a p -amino-phenylalanine ( p AF)-based relay system that enables site-specific functionalization of proteins without chemical synthesis of the building blocks. p AF was biosynthesized under optimized conditions, followed by site-specific incorporation into a specific protein residue. The resulting protein was ready for functionalization using an oxidative conjugation reaction. We demonstrated the use of this relay system by preparing a fluorophore-labeled anti-HER2 single-chain variable fragment antibody for fluorescent imaging.